Музей визвольної боротьби України і сучасний стан його фондів - Мушинка, М. (Народна творчість та етнографія, 2005)
The article discusses the history of rise and development of the Museum of Liberation Movement of Ukraine in Prague, which is the least known Ukrainian institution during the time betweeen wars and a war period. It contained unique materials, that later were taken to the Soviet Union. One part of them dissapeared. The rest of the fonds was scattered in the archives of the USSR and Ukraine. The access to them was restricted, and only nowadays different establishments plan or start publishing catalogues of the museum.